Molecular titanium nitrides: nucleophiles unleashed - Grant, Lauren N. (Royal Society of Chemistry, 2017)

(untitled) (Chem Sci)
In this contribution we present reactivity studies of a rare example of a titanium salt, in the form of [μ(2)-K(OEt(2))](2)[(PN)(2)Ti[triple bond, length as m-dash]N](2) (1) (PN(–) = N-(2-(diisopropylphosphino)-4-methylphenyl)-2,4,6-trimethylanilide) to produce a series of imide moieties including rare examples such as methylimido, borylimido, phosphonylimido, and a parent imido. For the latter, using various weak acids allowed us to narrow the pK (a) range of the NH group in (PN)(2)Ti[triple bond, length as m-dash]NH to be between 26–36. Complex 1 could be produced by a reductively promoted elimination of N(2) from the azide precursor (PN)(2)TiN(3), whereas reductive splitting of N(2) could not be achieved using the complex (PN)(2)Ti[double bond, length as m-dash]N[double bond, length as m-dash]N[double bond, length as m-dash]Ti(PN)(2) (2) and a strong reductant. Complete N-atom transfer reactions could also be observed when 1 was treated with ClC(O)(t)Bu and OCCPh(2) to form NC(t)Bu and KNCCPh(2), respectively, along with the terminal oxo complex (PN)(2)Ti[triple bond, length as m-dash]O, which was also characterized. A combination of solid state (15)N NMR (MAS) and theoretical studies allowed us to understand the shielding effect of the counter cation in dimer 1, the monomer [K(18-crown-6)][(PN)(2)Ti[triple bond, length as m-dash]N], and the discrete salt [K(2,2,2-Kryptofix)][(PN)(2)Ti[triple bond, length as m-dash]N] as well as the origin of the highly downfield (15)N NMR resonance when shifting from dimer to monomer to a terminal nitride (discrete salt). The upfield shift of (15)N(nitride) resonance in the (15)N NMR spectrum was found to be linked to the K(+) induced electronic structural change of the titanium-nitride functionality by using a combination of MO analysis and quantum chemical analysis of the corresponding shielding tensors.